2017
DOI: 10.5194/cp-2017-114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vegetation history and palaeoclimate at Lake Dojran (FYROM/Greece) during the Late Glacial and Holocene

Abstract: Abstract.A new high-resolution pollen and NPPs (Non-Pollen Palynomorphs) analysis has been performed on the sediments of Lake Dojran, a transboundary lake located at the border between Greece and Former Yugoslavian Republic of Macedonia (FYROM). The sequence covers the last 12500 years and provides information on vegetational dynamics of the Late Glacial and Holocene for southern Balkans. A robust age-model, sedimentological, diatom, and biomarker analyses published previously have been the base for a multi-pe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A gap in shell fragment data (7.7-2.7 cal kyr BP) is probably due to a high lake level increasing the distance from coring location to the shore, thereby reducing the focussing of shell material and widening the non-habitable zone in the central basin due to a finer substrate. In the late Holocene, a lower lake level is suggested by fewer planktonic diatoms (Zhang et al, 2014), and is consistent with lower temperatures and a regional shift to drier conditions (Roberts et al, 2008;Thienemann et al, 2017). A change to higher δ 13 C is likely due to reduced water input (less soil CO2 inflow) and a lower precipitation to evaporation ratio, both driving higher δ 13 CDIC.…”
Section: Comparison With Multi-proxy Data From Co1260mentioning
confidence: 57%
See 4 more Smart Citations
“…A gap in shell fragment data (7.7-2.7 cal kyr BP) is probably due to a high lake level increasing the distance from coring location to the shore, thereby reducing the focussing of shell material and widening the non-habitable zone in the central basin due to a finer substrate. In the late Holocene, a lower lake level is suggested by fewer planktonic diatoms (Zhang et al, 2014), and is consistent with lower temperatures and a regional shift to drier conditions (Roberts et al, 2008;Thienemann et al, 2017). A change to higher δ 13 C is likely due to reduced water input (less soil CO2 inflow) and a lower precipitation to evaporation ratio, both driving higher δ 13 CDIC.…”
Section: Comparison With Multi-proxy Data From Co1260mentioning
confidence: 57%
“…Increasing water depth and higher trophic levels are also indicated by a shift to a plankton-dominated diatom assemblage (Figure 5; Zhang et al, 2014). A change to lower δ 13 C under higher trophic levels suggests δ 13 CDIC is likely a function of increasing catchment soil development (higher AP; Masi et al, 2017;Rothacker et al, 2018), and the delivery of respired soil CO2 with low δ 13 C (as suggested for nearby Lake Ohrid; Lacey et al, 2015). A gap in shell fragment data (7.7-2.7 cal kyr BP) is probably due to a high lake level increasing the distance from coring location to the shore, thereby reducing the focussing of shell material and widening the non-habitable zone in the central basin due to a finer substrate.…”
Section: Comparison With Multi-proxy Data From Co1260mentioning
confidence: 95%
See 3 more Smart Citations